2016
DOI: 10.1007/s10903-015-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Self-Reported Family Health History of Breast Cancer

Abstract: The objective of this study was to identify predictors of self-reported family health history of breast cancer in an ethnically diverse population of women participating in a breast cancer screening program. Participants completed a self-administered questionnaire about their demography, health, breast health and family health history of breast cancer. The association between family health history of breast cancer and categorical variables were analyzed using the T test, chi square, and multi-nominal logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, there were some notable findings including that African Americans reported a family history of breast cancer significantly less frequently when compared to Caucasians. A significant difference was not found between Hispanics and Caucasians (Ricks‐Santi et al, 2016). Findings also noted trends between increased education and an increase of reporting a family history of breast cancer (Ricks‐Santi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were some notable findings including that African Americans reported a family history of breast cancer significantly less frequently when compared to Caucasians. A significant difference was not found between Hispanics and Caucasians (Ricks‐Santi et al, 2016). Findings also noted trends between increased education and an increase of reporting a family history of breast cancer (Ricks‐Santi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A significant difference was not found between Hispanics and Caucasians (Ricks‐Santi et al, 2016). Findings also noted trends between increased education and an increase of reporting a family history of breast cancer (Ricks‐Santi et al, 2016). Although this study did assess the frequency of cancer reporting in the family history, it only included questions about breast cancer and included few Caucasians for comparison.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Survey studies have also shown that black women are less likely to have breast cancer family history information available compared with white women. 8,9 The USPSTF BRCA risk assessment recommendation does not delineate the breast cancer hereditary susceptibility issues associated with African ancestry owing to lack of evidence. Paradoxically, the data-driven basis for the USP-STF recommendation statement may magnify existing genetic testing disparities.…”
mentioning
confidence: 99%
“…Higher rates of BRCA variants of uncertain significance are reported in non-Hispanic black individuals . Survey studies have also shown that black women are less likely to have breast cancer family history information available compared with white women . The USPSTF BRCA risk assessment recommendation does not delineate the breast cancer hereditary susceptibility issues associated with African ancestry owing to lack of evidence.…”
mentioning
confidence: 99%